A Rare Case Report on Post Stroke Vertical Gaze Palsy - Aakanksha Sharma; Neha Mohammed; Indu Bala (Asian Journal of Medical Research, 2023)
Vertical gaze palsy is mainly a manifestation of midbrain lesions. We report the case of a 56-year-old man who presented to our facility with vertical gaze palsy and on investigation thalamic infarct was documented on MRI brain. The etiology of infarct was small vessel disease due to hypertension and diabetes after excluding other causes for the manifestations.